Selective flotation of lepidolite from albite and quartz using a Hyperbranched surfactant THQ-8: Insights through foam property and adsorption behavior - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Constructing a dual-active-phase Li4SiO4/Li3NaSiO4 system through Na2CO3/NaCl codoping for enhanced thermochemical energy storage - Jian Chen; Rui Shen; Yan Qi; Hanlei Yu; Tao Fang; Xue Bu; Ziheng Xu; Han Ye; Youshi Li; Bocheng Yu; Hui Zhou (Chemical Engineering Journal, 2026)

Flotation of quartz from albite using oligomeric surfactant THQ-8 in synergy with NaOL - Yukun Wu; Lingfeng Shen; Rui Xu; Ning Sun; Li Wang (Minerals Engineering, 2026)

Estimation of ultimate bearing capacity for geosynthetic-reinforced sandy soil foundations by physics-informed deep learning model - Geye Li; Chungsik Yoo; Panpan Shen; Qingming Wang; Minmin Luo; Rui Zhang; Chao Xu (Geotextiles and Geomembranes, 2026)

All-in-one ionic hydrogel for wearable strain sensing and moisture electricity generation - Xinlei Wang; Bin Li; Qi Zeng; Yufan Mao; Zechao Han; Gangli Zhao; Shuaiqi Han; Dingyun Zhang; Jiaxing Huo; Rui Xu; Daozhi Shen (Chemical Engineering Journal, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

A novel LSTM-Kriging model for spatiotemporal interpolation of air pollution - Rui Xu; Jiaming Zou; Yuanfeng Sun; Jian Li; Liyi Guo; Shiming Shen; Hang Wan (Air Quality, Atmosphere & Health, 2026)

Generalized traverse task scheduling based on THRO algorithm for AUV with energy-constrained - Qixin Sha; Rui Nian; Jiaming Zhang; Xiaoting Xu; Yue Shen; Bo He (Ocean Engineering, 2026)

Underestimation of industrial contributions to VOC fluctuation in the Hangzhou Bay: Insights from simultaneous measurements and ML-SHAP analysis - Kun Hu; Song Guo; Lei Shen; Zichao Wan; Xinshi Ni; Rui Tan; Xudong Tian; Bingye Xu; Limin Zeng; Qingyan Fu; Min Hu; Sihua Lu (Environmental Pollution, 2026)

Experiments of orthometric height determination by transportable clock referred to GNSS time - Lei Wang; Lihong Li; Pengfei Zhang; Wei Xu; An Ning; Rui Xu; Ziyu Shen; Kuangchao Wu; Wenbin Shen (Advances in Space Research, 2026)

One-step hydrothermal synthesis of Sm-doped BiOIO3 for enhanced photocatalytic removal of mercury from flue gas - Yixuan Shen; Zijian Xiang; Jiang Wu; Sheng Wang; rui Zhu; Yaji Huang; Shaohua Liang; Jingxin Xu; Xueli Sun; Xiuyong Zhao (Fuel, 2026)

Pore Connectivity and Its Pattern in Gas Shale Reservoirs - Rui Yang; Sijun Cheng; Zhiliang He; Qinhong Hu; Baojian Shen; Pengwei Wang; Jianting Xu (Journal of Earth Science, 2026)

Efficient combined use of electroacupuncture with ordered collagen scaffolds enhances the therapeutic efficacy of human spinal cord-derived neural progenitor cells therapy in spinal cord injury rats - Yunlong Zou; Weiwei Xue; Bo Guo; Lu Li; Yannan Zhao; Xianming Wu; Zhifeng Xiao; Qi Zhang; Dezun Ma; Xinhao Zhao; Bing Chen; He Shen; et al. (Science China Life Sciences, 2026)

How does low air pressure affect the combustion performance of nano-thermite systems? - Linyan Shen; Zhengwu Dong; Rui Zhang; Yuxuan Zhou; Yueting Wang; Keer Ouyang; Jianbing Xu; Yinghua Ye; Ruiqi Shen (Fuel, 2026)

Perspective on the sustainable development of a novel high-salinity coal mine water treatment technology - Zhou Shen; Xiaotong Zou; Yisa Li; Rui Lu; Maiqi Xiang; Kaiwei Xu (Desalination, 2026)

Evaluation of landfill leachate treatment efficiency using a three-dimensional electrode wastewater purification system - Kai Song; Feiyu An; Meng Shen; Yinqi Chen; Yulong Lu; Rui Zhao; Xu Ren (Journal of Water Process Engineering, 2026)

Critical thresholds in urbanization-vegetation dynamics: Multiscale remote sensing evidence from Chinese cities - Yining Shen; Nan Wang; Yunyan Du; Jiawei Yi; Sheng Huang; Wenna Tu; Peixian Luo; Rui Xu; Dingchen Hu (Journal of Environmental Management, 2026)

Inhibiting NAT10 suppresses hepatocellular carcinoma progression by reducing Nrf2 mRNA stability and increasing oxidative stress - Wei Gu; Ziyi Ren; Jie Gao; Ziyi Shen; Yuanhui Wang; Luanqi Xu; Rui Qian; Qinyi Miao; Yifan Wu; Xiaomeng Hu; Yan Wu; Wei Liu; et al. (Chemico-Biological Interactions, 2026)

Hidden potential of rare root endophytes in native plants for phytoremediation in antimony mine tailings - Hanbing Gao; Zhaohui Guo; Shikai Li; Chi Zhang; Min Shen; Xiao He; Rui Xu (Plant and Soil, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Measuring intercontinental-scale geopotential difference using atomic clock frequency comparison with PPP technique - Kuangchao Wu; Wen-Bin Shen; Hok Sum Fok; Zengzeng Lian; Pengfei Zhang; Lihong Li; Lei Wang; An Ning; Rui Xu; Ziyu Shen (Advances in Space Research, 2026)

Enhancement mechanism of metal ions on lepidolite flotation in mixed NaOL/DDA system - Rui Xu; Lingfeng Shen; Jinghua Huang; Honghu Tang; Haisheng Han; Wei Sun; Li Wang (Minerals Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Core microbiota with antimonite oxidation coupled nitrogen fixation traits persist in the rhizosphere of pioneer plants in antimony tailings - Hanbing Gao; Zhaohui Guo; Fenglian Huang; Shikai Li; Xiao He; Jaovola Ulrich Fernio; Wei lv; Ling Zhou; Shuyang Du; Min Shen; Rui Xu (Environmental Research, 2025)

Air pollution, drought, and their synergistic effects on cardiovascular disease risk in China: a nationwide study - Chaohao Ling; Rui Li; Qian Shen; Lulu Cui; Mangen Yang; Zhou Liu; Tianzhao Xu; Wenwen Sun; Shaofu He (Environmental Pollution, 2025)

Changes and responses of GPP among different plant functional types in a savanna ecosystem under future climate scenarios - Weiduo Chen; Xuehai Fei; Jingyu Zhu; Rui Chen; Haiqiang Du; Yingqian Huang; Yong Zhang; Yi Shen; Aping Niu; Peng Xu (Journal of Environmental Management, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Carbon-friendly design method of tunnel lining segments based on Pareto optimal analysis - Tao Liu; Hehua Zhu; Yi Shen; Liankun Xu; Yi Rui (Tunnelling and Underground Space Technology, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Human dental follicle cell-derived conditioned media enhance periodontal regeneration by regulating the osteogenic differentiation and inflammation of periodontal ligament stem cells and macrophage polarization - Yichen Gao; Xianyi He; Yuyao Deng; Xia Wang; Jie Shen; Wei Xu; Rui Cai; Xiaorong Lan; Junliang Chen; Yun He (Molecular and Cellular Biochemistry, 2025)

Toxic effects and transcriptome analysis of the early life stages of Larimichthys crocea exposed to the bloom-forming dinoflagellate Alexandrium tamarense - Yongqi Cai; Anglu Shen; Hongtao Liu; Chongfeng Liu; Wantu Xu; Rui Jia (Marine Environmental Research, 2025)

Self-luminescent dual-ligand metal-organic framework based electrochemiluminescence probes for organophosphorus pesticides determination - Zheng Shen; Rui Xu; Guangxian Wang; Haifang Wang; Deyan Xu; JingJing Liu; Guanjie Wang; Yemin Guo; Xia Sun (Food Chemistry, 2025)

NIR-activatable proenzyme DSF/CuS@M for synergistic in situ chemotherapy/CDT/PTT/cuproptosis-based antitumor therapy - Lushuang Xu; Qinyue Chen; Yangwei Qian; Jin Wang; Chenxi Wang; Rui Fan; Jia-Wei Shen; Qiying Shen (Chemical Engineering Journal, 2025)

Ionic covalent organic framework engineered super-charged thin-film composite polyamide membrane for desalination - Hui Wang; Rui Ding; Tao Wu; Xianjuan Zhang; Lijuan Cheng; Kai Xu; Yu Zheng; Xiao Pang; Genliang Ji; Liqiang Shen; Junjun Li; Runnan Zhang; et al. (Chemical Engineering Journal, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Isolation and detection strategies for decoding the heterogeneity of extracellular vesicles - Shi-Ming Wang; Dan Wang; Yu-Qing Shen; Mo-Han Wang; Fei Jia; Zhao Pan; Liang Dong; Xian-Yu Zheng; Hui-Qin Wen; Rui Xu (Chemical Engineering Journal, 2025)

Methodology for quality risk prediction for milk powder production plants with domain-knowledge-involved serial neural networks - Kaiyang Chu; Rui Liu; Xu Shen; Guijiang Duan (Food Chemistry, 2025)

Numerical investigation on the suction caisson response considering seabed trenches and cyclic loading - Le Wang; Tingran Zhang; Xinglei Cheng; Wanhai Xu; Zhichao Shen; Shengjie Rui; Yinghui Tian (Ocean Engineering, 2025)

PET/CT-guided and OPN-targeted melanin nanoparticle platform for early diagnosis and precision therapy of idiopathic pulmonary fibrosis (IPF) - Jie Ji; Jie Sheng; Pengjun Zhang; Feng Wang; Yutong Xu; Xingyue Feng; Rui Xu; Yi Shen; Longjiang Zhang; Xiaodong Han (Chemical Engineering Journal, 2025)

The impact of Neoporphyra haitanensis dietary supplement on astaxanthin esters and fatty acids accumulation associated with immune promotion in Pacific white shrimp (Litopenaeus vannamei) - Qian Shen; Shuang Li; Shuyu Zhang; Jiaming Xu; Haimin Chen; Qijun Luo; Rui Yang; Juanjuan Chen (Aquaculture, 2024)

Experimental Study on the Classification and Evolution of the Tip Cavitation Morphology in Axial Waterjet Pumps with Two Different Blade Numbers - Xi Shen; Haoran Wu; Gang Yang; Rui Tang; Chenxin Chang; Bin Xu; Suben Lin; Desheng Zhang (Journal of Marine Science and Engineering, 2024)
Tip leakage flow and induced unstable cavitation can significantly damage the performance of axial waterjet pumps. This study investigated the impact of blade numbers on cavitating conditions in an axial waterjet pump by conducting tests of performance characteristics and high-speed photography experiments on three-blade and four-blade impellers. The results showed that the critical cavitation number σc of the three-blade impeller was larger, while the four-blade impeller flow pattern deteriorated more rapidly after σc. Various cavitation structures in the tip region were observed under different conditions, including clearance cavitation, shear layer cavitation, tip leakage vortex cavitation, and suction-side-perpendicular cavitating vortices (SSPCVs). Tip cavitation maps of the test impellers were drawn based on the flow rate coefficient and cavitation number variation. The three-blade impeller exhibited a wider range of severe cavitation, particularly with an increased occurrence of SSPCVs. With the cavitation number and flow rate coefficient decreased, the SSPCV generated from triangular cavitation cloud shedding presented an increased trend in scale and quantity. Conversely, in the case of the four-blade impeller, SSPCVs were often disrupted by the adjacent blade during migration and interfered with the tip cavitation in the neighboring flow passage.

Extracellular vesicles in pulmonary infection: From pathophysiology to theranostic technologies - Xu Wang; Mai-Qing Shi; Yang Wang; Hao Zhou; Ke Peng; Jun Wang; Shi-Kun Sun; Xu-Rui Shen; Jia-Jia Wang; Zhi Zhao; Xian-Guang Ding; Fu-Hai Ji (Chemical Engineering Journal, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

Redox-active poly(imide-quinone) covalent organic framework anodes for high-efficient and durable aqueous proton batteries - Yao Miao; Wei Jin; Mengna Qin; Yong-Miao Shen; Yanli Chen; Tai-Rui Wu; De-Yin Wu; Juan Xu; Jianyu Cao (Chemical Engineering Journal, 2024)

Meteoric diagenesis influenced by East Asian Summer Monsoon: A case study from the Pleistocene carbonate succession, Xisha Islands, South China Sea - Lü Wu; Rui Wang; Kefu Yu; Min Ren; Simone Booker; Ruoxia Shen; Wei Jiang; Shendong Xu; Tianlai Fan; Songye Wu; Qiushuang Qin; Xingchi Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Synthesis of amorphous-MnO2/Clinoptilolite and its utilization for NH4+-N oxidation in an anoxic environment - Caocong Liu; Yiyuan Zhuo; Yuzhe Chen; Yuanxiang Mao; Qiushi Shen; Jiangsen Ma; Rui Ma; Linsong Cheng; Fangying Ji; Xiaoyi Xu (Environmental Research, 2024)

Induction of Anxiety-Like Phenotypes by Knockdown of Cannabinoid Type-1 Receptors in the Amygdala of Marmosets - Lin Zhu; Di Zheng; Rui Li; Chen-Jie Shen; Ruolan Cai; Chenfei Lyu; Binliang Tang; Hao Sun; Xiaohui Wang; Yu Ding; Bin Xu; Guoqiang Jia; et al. (Neuroscience Bulletin, 2023)

Identification of potential genetic causal variants for obesity-related traits using statistical fine mapping - Rui Gong; Jonathan Greenbaum; Xu Lin; Yan Du; Kuan-Jui Su; Yun Gong; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

A superstable, flexible, and scalable nanofluidic ion regulation composite membrane - Lianmeng Si; Yihan Wu; Hong Xiao; Wensi Xing; Rui Song; Yiju Li; Sha Wang; Xu Liang; Wenshan Yu; Jianwei Song; Shengping Shen (Science Bulletin, 2023)

Numerical study on unsteady cavitation flow and vortex dynamics characteristics around the Delft Twist 11 hydrofoil - Gang Yang; Xi Shen; Bin Xu; Qinghui Meng; Chengxin Chang; Rui Tang; Desheng Zhang (Ocean Engineering, 2023)

Intrinsic reaction selectivity between gaseous HCl and SO2 over ethanol-hydrated CaO adsorbent in coal-fired flue gas dechlorination - Xiaoshuo Liu; Rui Wang; Xinze Geng; Ao Shen; Cong Chen; Yifan Xu; Xunlei Ding; Yufeng Duan; Shilin Zhao (Chemical Engineering Journal, 2023)

Mn(VII) enhanced by CaSO3 to remove trace organic pollutants in high salt organic wastewater: Further enhancement of salinity - Linsong Cheng; Yuanxiang Mao; Lei Jiang; Rui Ma; Jiangsen Ma; Yiyuan Zhuo; Qiushi Shen; Caocong Liu; Liuwei Zhao; Xiaoyi Xu; Fangying Ji (Chemosphere, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Frequency effect on mechanical properties of calcareous sand under cyclic traffic loading - Xiaoxi Rui; Yang Shen; Yinghao Ma; Junhong Xu (Soil Dynamics and Earthquake Engineering, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

CuFe2O4/diatomite actuates peroxymonosulfate activation process: Mechanism for active species transformation and pesticide degradation - Peng Xu; Rui Wei; Peng Wang; Xiang Li; Chunyan Yang; Tianyao Shen; Tong Zheng; Guangshan Zhang (Water Research, 2023)

High adaptability and stability FeCo2O4/diatomite composite for efficient peroxymonosulfate activation: Performance, water matrix impact, and mechanism - Peng Xu; Xiang Li; Rui Wei; Chunyan Yang; Tianyao Shen; Peng Wang; Guangshan Zhang (Chemical Engineering Journal, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Disabled travel and urban environment: A literature review - Xiaoming Shen; Siqi Zheng; Rui Wang; Qinwei Li; Zike Xu; Xiaoliang Wang; Jiayu Wu (Transportation Research Part D: Transport and Environment, 2023)

Sedimentation of cohesive sediments at the subtidal flat affected by wind wave in high turbidity estuary - Qi Shen; Qin Zhu; Shuguang Liu; Sha Lou; Hualin Wu; Zhenchang Zhu; Bin Xu; Rui Yuan (Frontiers in Marine Science, 2023)
Sedimentation is an important mechanism to mitigate the shrinking of tidal flat and to restore its ecological function by means of sand or mud nourishment. To explore the sedimentation of cohesive sediments, a seabed tripod observation system was deployed at the subtidal region of the Hengsha Shoal adjacent to the turbidity maximum zone of the Yangtze Estuary for 11 days. The results showed that the fine sediment with the median grain size around 8 mm occupied the whole water column. The seabed was in relative equilibrium state with the fluctuation of bed level smaller than 16 mm during the moderate wind condition while the seabed experienced a rapid erosion of 38mm and a successive intensive accretion of 68mm during the process of wind wave and swell. The bottom hydrodynamic at 0.3mab during the bed accretion was stronger than that during the bed erosion. The deposition process of cohesive sediments can be better described by the simultaneous deposition paradigm than that by the exclusive deposition paradigm according to the direct data-model comparison of the bed level changes, especially during the impact of fluid mud. Three possible reasons for the better performance of the simultaneous deposition paradigm were proposed. The first possibility is that the fine suspended sediments do maintain a continuous contact with the sediment bed since the direct bed level changes during our observation period has been well reproduced by the simultaneous deposition paradigm. The second possibility is the SSC-induced turbulence damping which facilitates the fine sediment settling in the form of cohesive sediment flocs, indicating the settling of sediments can’t be judged by the critical shear stress for deposition just based on the single particle grain size. The last possibility is the fluid mud-induced overestimated bed shear stress by using turbulent velocity fluctuation above the fluid mud-water interface, which produces excess sediment erosion waiting to be compensated by the simultaneous deposition paradigm. For practical modeling purposes, modeling under the simultaneous deposition paradigm can give satisfactory results for the sedimentation of cohesive sediment especially during the impact of wave or swell.

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Hedgehog pathway is negatively regulated during the development of Drosophila melanogaster PheRS-m (Drosophila homologs gene of human FARS2) mutants - Lidangzhi Mo; Rui Li; Chunxia He; Qi Chen; Changwei Xu; Liangliang Shen; Kun Chen; Yuanming Wu (Human Cell, 2022)

A study on the infection status and transmission of avian leukosis virus subgroup J in Hy-line brown roosters - Fanfeng Meng; Qiuchen Li; Rui Han; Guanlong Xu; Xintao Gao; Fubing Luo; Guangnian Shen; Xiaodong Liu; Zhifang Zhang; Peng Zhao; Guozhong Zhang (Archives of Virology, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Polar Sea Ice Identification and Classification Based on HY-2A/SCAT Data - Rui Xu; Chaofang Zhao; Xiaochun Zhai; Ke Zhao; Jichang Shen; Ge Chen (Journal of Ocean University of China, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

High-throughput sequencing reveals the spatial distribution variability of microbial community in coastal waters in Shenzhen - Rui Zhang; Yu Liu; Xianfeng Zhao; Zhihui Zhao; Honglian Zhang; Xiaoping Huang; Weiqing Xu; Yuchun Shen; Wensheng Lan (Ecotoxicology, 2021)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

Decreasing intraocular pressure significantly improves retinal vessel density, cytoarchitecture and visual function in rodent oxygen induced retinopathy - Rui Du; Xu Wang; Ke Shen; Shigang He (Science China Life Sciences, 2020)

Effect of genotype and environment on agronomical characters of common vetch (Vicia sativa L.) - Rui Dong; Shu H. Shen; Mohamed Z. Z. Jahufer; De K. Dong; Dong Luo; Qiang Zhou; Xu T. Chai; Kai Luo; Zhi B. Nan; Yan R. Wang; Zhi P. Liu (Genetic Resources and Crop Evolution, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Comparisons of Evaluation Factors and Application Effects of the New [BQ]GSI System with International Rock Mass Classification Systems - Shen Yan-jun; Yan Rui-xin; Yang Geng-she; Xu Guang-li; Wang Shan-yong (Geotechnical and Geological Engineering, 2017)

Site-directed mutagenesis under the direction of in silico protein docking modeling reveals the active site residues of 3-ketosteroid-Δ1-dehydrogenase from Mycobacterium neoaurum - Ning Qin; Yanbing Shen; Xu Yang; Liqiu Su; Rui Tang; Wei Li; Min Wang (World Journal of Microbiology and Biotechnology, 2017)

Capecitabine plus oxaliplatin (XELOX) compared with 5-fluorouracil/leucovorin plus oxaliplatin (FOLFOXs) in advanced gastric cancer: meta-analysis of randomized controlled trials - Hong-Bin Xu; Fang Huang; Rui Su; Fu-Ming Shen; Qian-Zhou Lv (European Journal of Clinical Pharmacology, 2015)

Rheological Characteristics of Weak Rock Mass and Effects on the Long-Term Stability of Slopes - Tianhong Yang; Tao Xu; Hongyuan Liu; Chunming Zhang; Shanyong Wang; Yongqin Rui; Li Shen (Rock Mechanics and Rock Engineering, 2014)

The metabolism of 8-heptadecene in Pyropia (Bangiaceae, Rhodophyta) - Min Zhang; Rui-Xia Li; Chuan-Ming Hu; Li-En Yang; Jun Tang; Qin-Qin Lu; Tao Zhang; Zong-Gen Shen; Song-Dong Shen; Pu Xu; Jian-Yi Zhu (Journal of Applied Phycology, 2014)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Analysis on the interaction between IL-1F7 gene and environmental factors on patients with ankylosing spondylitis: a case-only study - Rui Ge; Faming Pan; Fangfang Liao; Guo Xia; Yang Mei; Beibei Shen; Tianchen Zhang; Jing Gao; Li Zhang; Zhenhua Duan; Shengqian Xu; Jianhua Xu (Molecular Biology Reports, 2011)

RETRACTED ARTICLE: Cytotoxic activities of tubeimoside-2 on human hepatoma HepG2 cells by induction of G2/M phase arrest and apoptosis in a p53-dependent manner - Ying-Yong Zhao; Xu Chao; Yongmin Zhang; Li-Jun Sun; Hong Zhang; Rui-Chao Lin; Xuefeng Shen; Wen-Ji Sun (Apoptosis, 2010)

A new dolabellane diterpenoid from the Hainan soft coral Spongodes sp. - Xiao-Hong Yan; Rui Jia; Xu Shen; Yue-Wei Guo (Natural Product Research, 2007)

Functional response of the predator Scolothrips takahashii to hawthorn spider mite, Tetranychus viennensis: effect of age and temperature - Li Ding-Xu; Tian Juan; Shen Zuo-Rui (BioControl, 2007)